The Employment Equity Act, 1998 (and other myths about the pursuit of "equality", "equity" and "dignity" in post-apartheid South Africa) (Part 1) - Andre M Louw (Potchefstroom Electronic Law Journal, 2015)
The author critically examines the organising principle of the affirmative action provisions of the Employment Equity Act (or EEA), as well as the implications of the recent judgment by the Constitutional Court in its first case involving the application of affirmative action in the employment context (and in terms of the EEA) – SAPS v Solidarity obo Barnard. While reiterating the need for restitutionary measures such as affirmative action in South Africa, the author concludes – probably quite controversially - that the EEA's treatment of affirmative action has nothing to do with the equality right in the Bill of Rights, and that the Act pursues a different (and omnipresent) social engineering agenda by the state. The author calls for this realisation to prompt future affirmative action cases arising from the application of this Act to be removed from the scheme of (and potential defences available under) the equality jurisprudence, and for the courts to critically interrogate the constitutionality of the EEA's affirmative action scheme within its own context. The author believes that Chapter III of the Act is unconstitutional in this sense, and he calls for the scrapping of its provisions. He also calls for a (more) constitutionally-compliant exposition from the Constitutional Court of the parameters of legitimate affirmative action under the Bill of Rights, and adds his voice to the numerous calls for reconsideration of the "rationality test" expounded in Minister of Finance v van Heerden. More generally, the author considers the apparently all-pervasive application of the government ideology of the pursuit of demographic representivity in "transformation" of employment and other contexts (expressing grave doubts about its constitutionality along the way).